Effect of sprinkler irrigation on the properties of leached chernozem and the yield of Bromopsis inermis Leyss. in the Southern Cis-Ural - Alexander Komissarov; Mikhail Komissarov; Irek Minniakhmetov; Oleg Lykasov; Julia Afanasyeva (Plant, Soil and Environment, 2021)
The paper examines the effect of the long-term (10 years) low-intensity sprinkler irrigation on the properties of leached chernozem soils covered with Bromopsis inermis Leyss. (BIL) stands in the Southern Cis-Ural forest-steppe. The study analysed changes in the soil's agrophysical and chemical properties. As a result of long-term irrigation, the humus horizon (A + AB) thickness increased by 16 ± 3 cm; the organic carbon (Corg) content and nutrients decreased in this rooting zone, in particular, Corg by 0.3%, available phosphorus by 24.8 mg/kg, exchangeable potassium by 18.4 mg/kg and the stock of Corg by 16 t/ha. The particle size distribution of irrigated soil did not significantly changed; some changes were observed for the soil's aggregate composition. The soil's hydrophysical properties, water and air regime worsened.